America the possible : manifesto for a new economy - Speth, James Gustave (Yale University Press, 2012)
"In this third volume of his award-winning American Crisis series, James Gustave Speth makes his boldest and most ambitious contribution yet. He looks unsparingly at the sea of troubles in which the United States now finds itself, charts a course through the discouragement and despair commonly felt today, and envisions what he calls America the Possible, an attractive and plausible future that we can still realize. The book identifies a dozen features of the American political economy--the country's basic operating system--where transformative change is essential. It spells out the specific changes that are needed to move toward a new political economy--one in which the true priority is to sustain people and planet. Supported by a compelling "theory of change" that explains how system change can come to America, the book also presents a vision of political, social, and economic life in a renewed America. Speth envisions a future that will be well worth fighting for. In short, this is a book about the American future and the strong possibility that we yet have it in ourselves to use our freedom and our democracy in powerful ways to create something fine, a reborn America, for our children and grandchildren"--Provided by publisher.